2020
DOI: 10.1111/nhs.12791
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision‐making for women facing an unplanned pregnancy: A qualitative study

Abstract: This study aimed to explore the competencies of health care practitioners who promote shared decision-making (SDM)-based care for women facing an unplanned pregnancy in Japan. We conducted semistructured interviews with 12 care providers who are pioneers in care for women facing an unplanned pregnancy and adopted a modified grounded theory approach for data analysis. A three-step model for shared decision making in practice (team talk, option talk, and decision talk) was used as a reference. The answers given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Previously, we investigated the decision-making support experience of unplanned pregnancy of women through care providers (Ueno et al, 2020). The study suggested that women with unplanned pregnancies benefit from interventions designed to improve SDM and the need for IP-SDM modelÀbased care.…”
Section: Scale Creationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we investigated the decision-making support experience of unplanned pregnancy of women through care providers (Ueno et al, 2020). The study suggested that women with unplanned pregnancies benefit from interventions designed to improve SDM and the need for IP-SDM modelÀbased care.…”
Section: Scale Creationmentioning
confidence: 99%
“…One study reported that care providers involved with unplanned pregnancies could apply SDM to make autonomous decisions while restoring women's identity. (Ueno et al, 2020). Motivated by these observations on SDM, that study worked with parents and professionals to emphasize the need for midwifery care and improve its practice.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations